Life cycle cost analysis of an electric centrifugal chiller integrated with a district cooling plant - Hampo, C.C. (Taylor and Francis Ltd., 2021)
Electric Centrifugal Chillers (ECC) are mostly incorporated into District Cooling (DC) systems for charging the Thermal Energy Storage (TES) tank or/and to supply Chilled Water (CW) directly to the DC network for Air Conditioning (AC). ECC accounts for the highest percentage of the total electrical energy consumption, making it the most energy-intensive system in the DC setup. The high positive correlation between energy consumption and cost, and its influence on the decision-making process, necessitate the requirement to conduct an economic performance evaluation of the ECC plants. To achieve this objective, a Life Cycle Cost (LCC) analysis is performed to quantify the economic implication resulting from the ECC system's acquisition, operation, and maintenance. In this analysis, four (4) ECC systems installed in a large DC plant in Malaysia are considered the case study. The result obtained from the analysis of the study year revealed that April and June accounted for the maximum and minimum cost implication per outcome, respectively. It is also observed from the results that the climatic temperature conditions had a significant influence on the monthly cooling demand, energy consumed, and cost incurred. The operational phase of the system's life cycle accounted for the highest cost implication from the overall LCC result. A significant reduction in the operating cost is recorded as the indirect energy source used for driving the chiller plant is switched from the electricity supplied from the National Electricity Grid (NEG) and supplied from the Natural Gas Plant (NGP). The LCC per refrigeration ton of the ECC system is estimated to be MYR 1.44/RTh. The impact of system degradation (i.e. decrease in Coefficient of Performance (COP) value) over time on the overall cost per output refrigeration was also investigated. The study also revealed that operating an actual ECC system on electricity from NGP led to a 31 cost savings compared to an ideal system running on electricity from NEG. A sensitivity analysis is also conducted at the end of the study to determine the influence of the input variable on the output result. Â© 2021 Informa UK Limited, trading as Taylor & Francis Group.